Proceedings of the ACM Symposium on Applied Perception 2012
DOI: 10.1145/2338676.2338695
|View full text |Cite
|
Sign up to set email alerts
|

Apparent resolution enhancement for motion videos

Abstract: In this work we increase the apparent resolution of videos when viewed on a high-refresh rate display by making use of perceptual properties of the visual system. We achieve this enhancement by exploiting the viewer's natural tendency to track moving objects in videos which causes the screen pixels to be projected at different sub-pixel offsets onto the retina. We estimate the eye motion using optical flow and use it to compute multiple low-resolution frames for each input frame. By watching these new frames a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Within perception [Cornsweet 1970], phenomena such as edge enhancement, opponent-color theory, psychophysical reading aspects (e.g., [Legge et al 1985]), and numerous so-called visual illusions are exploited (e.g., [Wandell 1995;Pizlo et al 2007;Pizlo 2010]). Some approaches combine perceptually-based and ophthalmologically-based techniques for improving image viewing (e.g., [Peli and Woods 2009]) and for improving resolution in videos and animations (e.g., [Didyk et al 2010;Berthouzoz and Fattal 2012a;Berthouzoz and Fattal 2012b;Templin et al 2013;Stengel et al 2013]). For instance, the Cornsweet illusion has been exploited to provide enhanced local contrast [Ritschel et al 2008] and to provide a perceptually-based metric for achieving compelling and efficient stereo disparity [Didyk et al 2011].…”
Section: Perceptual and Rendering Approachesmentioning
confidence: 99%
“…Within perception [Cornsweet 1970], phenomena such as edge enhancement, opponent-color theory, psychophysical reading aspects (e.g., [Legge et al 1985]), and numerous so-called visual illusions are exploited (e.g., [Wandell 1995;Pizlo et al 2007;Pizlo 2010]). Some approaches combine perceptually-based and ophthalmologically-based techniques for improving image viewing (e.g., [Peli and Woods 2009]) and for improving resolution in videos and animations (e.g., [Didyk et al 2010;Berthouzoz and Fattal 2012a;Berthouzoz and Fattal 2012b;Templin et al 2013;Stengel et al 2013]). For instance, the Cornsweet illusion has been exploited to provide enhanced local contrast [Ritschel et al 2008] and to provide a perceptually-based metric for achieving compelling and efficient stereo disparity [Didyk et al 2011].…”
Section: Perceptual and Rendering Approachesmentioning
confidence: 99%
“…While Didyk et al [3] demonstrated the applicability of their approach only for linear motion, Templin et al [5] transformed it into an optimization problem which could be used for arbitrary motion in animations. Fattal et al combine this approach with a super-resolution PREVIOUS MODEL method to spatially enhance input videos that are at the display resolution [6] and formulate a perceived video model used in the optimization. Compared to this method in our approach we work with high-resolution videos as input to best possibly keep the originally available details.…”
Section: Related Workmentioning
confidence: 99%
“…Visual Attention In [5] and [6] optical flow is used for optimizing ADRE. However, movement is not the only attractor for visual attention.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A typical model consists of decomposing the high-resolution image to multiple low-resolution sub-images that are projected with an offset at a higher frame rate. [1,2,3]. The sub-images are then merged by the human visual system into a single high-resolution image that approximates the original high-resolution source.…”
Section: Introductionmentioning
confidence: 99%